The Microbial Ecology of a Hyper-Alkaline Spring, and Impacts of an Alkali-Tolerant Community During Sandstone Batch and Column Experiments Representative of a Geological Disposal Facility for Intermediate-Level Radioactive Waste. Issue 6 (2nd July 2016) - Smith, Sarah L.; Rizoulis, Athanasios; West, Julia M.; Lloyd, Jonathan R.
ABSTRACT: Naturally occurring hyper-alkaline springs and associated hyper-alkaline environments may have components that are analogous to a cement-based deep geological disposal facility (GDF) for intermediate level radioactive waste (ILW). Such high pH environments could give insights into the biogeochemical processes that could occur in the region of a GDF environment after the ingress of GDF-derived groundwater leads to the formation of a hyper-alkaline plume in the surrounding rock mass. This study focuses on the microbial community composition found at a highly alkaline spring near Buxton, Derbyshire, England, and the variation in community structure across spatially separated sample points of contrasting pH values (ranging from pH 7.5–13). Communities containing alkaliphilic and alkalitolerant bacteria were observed across the site by PCR amplification and 16S rRNA gene pyrosequencing and included members of the families Comamonadaceae and Xanthomonadaceae . At pH 13, the sequence library was dominated by Gammaproteobacteria of the families Pseudomonadaceae and Enterobacteriaceae . Bacterial communities from the site demonstrated the ability to reduce Fe(III) in microcosm experiments up to pH 11.5, suggesting the potential to reduce other metals and radionuclides of relevance to cement-encapsulated intermediate level radioactive waste (ILW) disposal. In laboratory column flow-through experiments, microbial communities present at the field site were also able to colonize crushed sandstone. Bacterial community composition varied between columns that had been supplied with alkali surface waters from the site amended with carbon (lactate and acetate, as proxies for products of cellulose degradation from ILW), and control columns that were not supplied with added carbon. Members of the family Clostridiaceae dominated the sequence library obtained from the carbon amended column inlet (45.8% of library), but became less dominant at the outlet (20.8%). Members of the family Sphingomonadaceae comprised 11.8% of the sequence library obtained from the control column inlet, but were not present in sediments collected from the column outlet, whereas the relative abundance of members of the family Comamonadaceae increased from the column inlet (35.2%) to the column outlet (57.2%). The spatial variation in community composition within the columns is indicative of discrete biogeochemical zonation in these flow-through systems.